The impact of environmental water on the potential application of core−shell titania−silica nanospheres as photocatalysts. (10th May 2021) - Cendrowski, Krzysztof; Pachnowska, Kamila; Augustyniak, Adrian; Wierzbicka, Jagoda; Pratnicki, Filip; Kucharski, Pawel; Kukułka, Wojciech; Mijowska, Ewa
Abstract: In this study, the core–shell silica nanospheres modified with titanium dioxide were tested in the photocatalytic decomposition of dyes. The presented data underlines the advantages and shortcomings in the potential application of silica-based catalysts to neutralize organic pollutants. During the photocatalytic reaction in distilled water, catalysts showed decreased efficiency due to a carbon layer deposited on its surface. This finding set an additional goal to investigate the possibility of regenerating the photocatalyst. Studies have shown that the catalyst could be successfully reused following the thermal removal of deposited carbon. Furthermore, the reactivated silica−titania catalysts exhibited comparable photocatalytic performance to the newly made nanomaterial. Surprisingly, catalyst application in the river water eventually resulted in the permanent deactivation of silica−titania nanospheres, which was caused by the interchangeable silica dissolution/precipitation process on the surface of the studied nanomaterial. In environmental water, silica dissolves and precipitates on titanium dioxide's surface, blocking the interaction between organic compounds and TiO2 . The deactivation occurring in the environmental samples is irreversible. In distilled water, the decomposition of organic compounds leads to photocatalysts' deactivation by forming a carbon layer on their surface. Reactivation of the silica-based photocatalyst after distilled water is achievable by annealing at a high temperature. In light of our findings, the combination of the photocatalytic properties of TiO2 and the silica template shows no prospects in the purification of polluted waste or environmental water.